In mice, discrete odors can selectively promote the neurogenesis of sensory neuron subtypes that they stimulate - Kawsar Hossain; Madeline Smith; Karlin E Rufenacht; Rebecca O'Rourke; Stephen W Santoro (eLife)
In mammals, olfactory sensory neurons (OSNs) are born throughout life, ostensibly solely to replace neurons lost via turnover or injury. This assumption follows from the hypothesis that olfactory neurogenesis is stochastic with respect to neuron subtype, as defined by the single odorant receptor that each neural precursor stochastically chooses out of hundreds of possibilities. This assumption is challenged, however, by recent findings that the birthrates of a fraction of OSN subtypes are selectively reduced by olfactory deprivation. These findings raise questions about how, and why, olfactory stimuli are required to accelerate the neurogenesis rates of some subtypes, including whether the stimuli are specific (e.g. discrete odorants) or generic (e.g. broadly activating odors or mechanical stimuli). Based on previous findings that the exposure of mice to sex-specific odors can increase the representations of subtypes responsive to those odors, we hypothesized that the neurogenic stimuli comprise discrete odorants that selectively stimulate OSNs of the same subtypes whose birthrates are accelerated. In support of this, we have found, using scRNA-seq and subtype-specific OSN birthdating, that exposure to male and exogenous musk odors can accelerate the birthrates of subtypes responsive to those odors. These findings reveal that certain odor experiences can selectively ‘amplify’ specific OSN subtypes and suggest that persistent OSN neurogenesis serves, in part, an adaptive function.